Porcine Abdominal Wall Simulator for Laparotomy Incision and Closure. (August 2015) - Khan, Sadaf; Cipriano, Cassie; Marks, Jeffrey M.; Schomisch, Steve J.
We describe an economical and simple abdominal wall model that provides a realistic experience for trainees as they develop the skills of creating an abdominal incision through the midline, followed by closure of the fascia and skin.